A Security Investigation Survey of Ransomware Detection and Avoidance Strategies for IoT Networks - Muhammad Nadeem; Syeda Wajiha Zahra; Muhammad Noman Abbasi; Ali Arshad; Saman Riaz; Waqas Ahmed (International Journal of Information Security Engineering, 2023)
The internet of things (IoT) refers to the interconnection of a large number of distinct physical objects, which in turn makes possible a variety of services and applications. Because the IoT sector is developing at such a rapid rate, ensuring its safety ought to be a high concern. At this time, ransomware attacks constitute the biggest danger to IoT posed by cyberattacks. Ransomware is software that blocks access to or usage of a victim’s computer and then demands money from the user in order to restore the machine to its previous state. In spite of the frequency of malware attacks, ransomware is considered to be the most devastating. This is due to the fact that it has caused companies to be interrupted, which has led to considerable cash loss while also creating a severe financial pressure on the organisation. Criminals may demand and collect extortion from victims while disguising their identities and whereabouts with the use of bitcoin, which is the most well-known cryptocurrency. A framework for the detection, prevention, and prediction of ransomware attacks has been established, and it is being used to conduct an analysis of various methodologies and tactics for detecting, preventing, and mitigating ransomware assaults.
Keywords: Detection; Internet of things (IoT); prediction; prevention; ransomware